2022
DOI: 10.1002/14651858.cd014959
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for leptospirosis

Abstract: To assess the beneficial and harmful e ects of antibiotics for the prevention of leptospirosis Antibiotic prophylaxis for leptospirosis (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…The use of antibiotics for leptospirosis may decrease the duration of clinical illness by 2–4 days, although this result was not statistically significant . The efficacy of treatment with antibiotics such as penicillin, doxycycline, azithromycin, or cephalosporins, commonly found in leptospirosis treatment regimes, did not seem to impact mortality or the duration of the fever. , Therefore, it was concluded that antibiotic therapy’s benefit in treating leptospirosis remains unclear, particularly for severe diseases . Therefore, antibiotics may not be used for mild cases in low-risk people.…”
Section: Introductionmentioning
confidence: 99%
“…The use of antibiotics for leptospirosis may decrease the duration of clinical illness by 2–4 days, although this result was not statistically significant . The efficacy of treatment with antibiotics such as penicillin, doxycycline, azithromycin, or cephalosporins, commonly found in leptospirosis treatment regimes, did not seem to impact mortality or the duration of the fever. , Therefore, it was concluded that antibiotic therapy’s benefit in treating leptospirosis remains unclear, particularly for severe diseases . Therefore, antibiotics may not be used for mild cases in low-risk people.…”
Section: Introductionmentioning
confidence: 99%